RONGGENG: CULTURAL ARTIFACTS AND ITS REPRESENTATION IN INDONESIAN'S FICTION - Yulianeta, Yulianeta (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2013)
This paper is based on the phenomenon of dancer or tayub which is celebrated as a verypopular cultural artifact in public life, particularly in Java. This tradition is originally partof a sacred ritual, which ultimately became a performing art, but tends to be viewed negatively.In a historical context, the dancer was originally seen based on cultural concept andevolves into culturally sacred profane.Negative reception of ronggeng is not only uttered orally but also embodied in the writtentradition. It is found in the genre of literary fiction such as in Tayuban’s Notosusanto Nugroho(1959), Sri Sumarah and Bawuk by Umar Kayam (1975), Trilogy Ronggeng DukuhParuk written Ahmad Tohari (1982), and Ronggeng works Dewi Lingga Sari (2007).The results of this study illustrate that the figure of dancer who is represented in Indonesianfiction are various. Although there are similarities, but the authors tend to have differentreception levels regarding ronggeng. Ronggeng as cultural artifacts is the manifestation ofthe ability of local communities to respond and adapt to the environment actively. Similarly,what is represented in fiction about ronggeng is a mirror of the society where the work wasborn.Keywords: prose fiction, reception, representation, ronggeng, tayub